Is waiting for rewards good for you? No association between impulsive choice, psychopathology, and functional outcomes in a large cohort sample - Patricia P. Bado; Giovanni A. Salum; Luis A. Rohde; Ary Gadelha; Pedro M. Pan; Eurípedes C. Miguel; Gail Tripp; Emi Furukawa (Wiley, 2024)
Abstract Background A stronger preference for immediate rewards has been reported in individuals with ADHD and other disorders. However, the consistency of the associations between this preference and psychiatric conditions as well as functional outcomes have been questioned. Research on its association with longitudinal outcomes is scarce. Methods The current study used data on a choice delay task (CDT) from a school‐based cohort of Brazilian children with those at higher risk for psychiatric disorders over‐sampled (n = 1917). The sample included typically developing children (n = 1379), those with ADHD (n = 213), and other disorders. The frequency of the trials where children chose a larger later reward versus a smaller sooner reward was compared for those with ADHD and typically developing children. Cross‐sectionally and longitudinally, the study also evaluated whether children's preference for larger delayed rewards at baseline predicted the presence of psychiatric disorders and functional life outcomes (academic performance, alcohol use, early pregnancy, criminal conviction, BMI). Results Children with ADHD and their typically developing peers performed similarly on the CDT. Their baseline task performance was not related to psychiatric conditions or life outcomes. Conclusions The current results raise questions regarding the use of the CDT with diverse populations and whether a preference for larger delayed rewards is predictive of positive long‐term outcomes as widely assumed.